The Effect of Architecture of Arts Education Tourism Towards Interest in Learning Arts for High School Students (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
The implementation of tourism activities not only has a purpose for traveling or entertainment. In education, tourism can have a function as a learning activity carried out by someone in their visit to a tourist attraction location. This study aims to determine the effect of organizing an art education tour on the interest in learning art for high school students. This study uses a quantitative research approach with a sample of 84 students who took part in an art education tourism program held at UPI (Indonesian University of Education). This study took a sample using total sampling techniques in which all respondents were taken into consideration the analysis of research data. Data collection used in this study is to use a closed questionnaire in the form of a scale. Research data analysis uses simple regression test data analysis techniques to find out whether there is an influence of art education tourism activities on high school studentsâ€™ interest in learning art at school. The results of the study can be concluded that educational tours have an influence on high school studentsâ€™ interest in learning art; this is indicated from the results of the coefficient of determination (R Square) of 0.479, which implies that the influence of educational programs on the dependent variable (interest in learning art) is 47.9%. The results of the analysis show how much the independent variable (X) can affect the dependent variable (Y).Â